Summation and reflection: my music education and conducting - Thayer, Patricia Ann (Kansas State University, 2020)
The purpose of this paper is to present my teaching philosophy, a lesson plan driven by the goals from the National Standards for Music as applied to the lesson, what the ensemble learned, the instructional strategies I used, what modifications I made, and a reflection of my growth and development as a music educator and conductor . Submitted with this report is a video presentation of a reading session, rehearsal, and performance of “Celebration of Life” by Australian composer Ralph Hultgren. This project was completed as a part of the requirements to meet the Master of Music degree, “Music Education Master’s Final Report” course at Kansas State University. As I reflect on the course of my studies in this Master’s program at Kansas State, I realize the profound impact my experiences have had on how I teach now compared to how I began my professional career in music education and conducting. This impact is most noticeable in my thought processes. I consider the ensemble’s instrumentation and ability, their background, and the way they learn, in-depth score study, and how I now design the rehearsal for greater efficiency. In my teaching, I strive to consistently share my passion for music and teaching while making everything I do for and about my students. The foundation of my philosophy of music education is “do your best, learn something, and most importantly, have fun.” I believe in music for everyone.
Keywords: Education; Rehearsal; Conducting; Standards; BandMusic